PENGARUH PERTUMBUHAN PERUSAHAAN , RASIO LIKUIDITAS, MATURITY, DAN RASIO AKTIVITAS TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN JASA - Widiastuti, Ni Putu Tresna; Rahyuda, Henny (E-Jurnal Manajemen; Vol 5 No 11 (2016), 2016)
Bond rating have an important role both for companies and investors as an indicator of default of a bond. This study aimed to determine the significance of variables influence the company's growth, the liquidity ratio, maturity, and the ratio of activity against bond rating services company in the Indonesia Stock Exchange (BEI) in the period 2012-2014. The population in this study is bond service company listed on the Stock Exchange the period 2012-2014 totaling 305 companies. The sampling technique used was purposive sampling, with a sample of 26 bond services company in BEI. The data analysis technique used is the logistic regression analysis. The results of the analysis showed that the partial growth and liquidity ratios have significant negative effect on the bond rating, maturity have significant positive effect on bond ratings, activity ratios not significant positive effect on the bond rating. Simultaneously the company's growth, the liquidity ratio, maturity, and the activity ratio have significantly influence bond rating.
Keywords: bond rating; the company' s growth; liquidity; maturity; activity ratio